Load response of biogas CHP systems in a power grid. (June 2021) - Ishikawa, Shiho; Connell, Nicholas O.; Lechner, Raphael; Hara, Ryoichi; Kita, Hiroyuki; Brautsch, Markus
Abstract: Renewable energy (RE) sources like wind and solar power have been introduced to power systems to make the energy market more sustainable and environmentally friendly. For this reason, the supply-demand mismatch in power systems is more severe than before, in terms of both frequency and magnitude. It is therefore necessary to reinforce the capability to make supply and demand adjustments in power grids. Here, we clarified the dynamic characteristics of biogas plants with combined heat and power (CHP) systems, that represent controllable RE power sources, and evaluated the possibility of using these systems as a new resource for supply-demand adjustments in the power grid. Additionally, the properties of the exhaust gas from the investigated CHP engines were measured as an environmental evaluation. We considered real-world biogas CHP systems operating in both Germany and Japan. Based on the results, biogas CHP systems have the potential to contribute to a long-term power equivalent adjustment such as tertiary control reserve (TCR) in Germany. However, these systems required several minutes between starting and stopping. Furthermore, increased emissions of methane and formaldehyde were measured when the CHP systems were starting up. We found that an operation with as few starts and stops as possible is therefore desirable. Highlights: Evaluation of the dynamic characteristics of actual biogas CHP systems. Investigation of load response with biogas CHP systems operating in Germany and Japan. Analysis of load adjustment as well as start-up and shut-down behavior of CHP systems. Measurement exhaust gas emissions during supply-demand adjustment. Biogas CHP systems can contribute to long-term power equivalent adjustment.